Stanovení poměru D- a L- forem kyseliny asparagové v lidských tkáních jako ukazatel věku - Pilin, Alexander; Bencko, Vladimír; Čabala, Radomír; Pudil, František; Sajdok, Jiří (Iga MZ ČR, 2001)
The research project deals with the estimation of the ratio of the D,Lforms of the aspartic acid in the correlat. with the age using the GC and HPLC chiral separat. and possible influence of the postmortal changes and anlytic. procedur. on the racemizat.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: dentin; biochemie; Age Determination by Teeth; soudní lékařství; Age Determination by Skeleton; kyselina asparagová; racemasy a epimerasy; určení zubního věku; Aspartic Acid; určení kostního věku; Racemases and Epimerases; Dentin